The effect of training methods and motivation on the mastering of pencak silat single category - Galih Satria Satria; Herman Subarjah; Indra Safari (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
In this study, the author aims to determine the relationship between random practice and block practice training methods with single category pencak silat skills. The method used by this researcher is a factorial experimental method to determine the effect of the training methods used on the skills of martial arts mastery. the single category of the Satria Muda Indonesian pencak silat college. In this study, the researcher used a sampling technique, namely purposive sampling with the number of samples taken as many as 20 people with the research instrument to measure the mastery of single category pencak silat moves. From the data, the results of data processing show that the values ​​in the pretest and posttest scores of all groups are greater than 0.05 with the value of each group (1) 0.794, (2) 0.083, (3) 0.119, (4) 0.875. Then the sentence hypothesis shows that the data is normally distributed. Then on the correlation value between the method and the skill level of mastery of pencak silat in the group when there is a motivation variable of rsquare = 0.654 so that it can be concluded that when the athlete is given a treatment, the mastery of the moves increases by 65.4% then the value between the correlation between method and skill level of pencak silat mastery in the group when there is no motivation variable, the value of rsquare = 0.319 is obtained so that from the data shows that there is an increase of 31.9%. So it can be concluded that there is a relationship between training methods and motivation on the ability of single category pencak silat skills